An Investigation into Fatigue Sensor Design and Modeling (Comprehensive Journal of Science, 2025)
Fatigue sensors are used as Structural Health Monitoring (SHM) mechanisms to detectdamage on struc- tural components before any failures occur. In this study, a U-notchedfatigue sensor was designed and analyzed to predict the fatigue life before catastrophic failureoccurs. The ANSYS workbench software and 7075-T6 aluminum alloy were used to modeland analyze our U-notch type fatigue sensor. The sensor model consisted of four beams of305 × 76.2 × 1.6 mm (length × width × thickness) dimensions with different fatigue U-notchradii. It was observed that fatigue life increased with an increase in the U-notch radius.However, the value of the maximum equivalent stress decreased with an increase in the notchradius. In addition, fatigue damage occurred around the U-notch radius when the U-notchradius was equal to or less than 6.4 m
Keywords: ANSYS software Fatigue sensor Health monitoring U-notch sensor